12/15-lipoxygenase orchestrates the clearance of apoptotic cells and maintains immunologic tolerance. - Uderhardt, Stefan; Herrmann, Martin; Oskolkova, Olga V.; Aschermann, Susanne; Bicker, Wolfgang; Ipseiz, Natacha; Sarter-Zaiss, Kerstin; Frey, Benjamin; Rothe, Tobias; Voll, Reinhard; Nimmerjahn, Falk; Bochkov, Valery N.; et al. (Immunity, 2012)
Noninflammatory clearance of apoptotic cells (ACs) is crucial to maintain self-tolerance. Here, we have reported a role for the enzyme 12/15-lipoxygenase (12/15-LO) as a central factor governing the sorting of ACs into differentially activated monocyte subpopulations. During inflammation, uptake of ACs was confined to a population of 12/15-LO-expressing, alternatively activated resident macrophages (resMΦ), which blocked uptake of ACs into freshly recruited inflammatory Ly6C(hi) monocytes in a 12/15-LO-dependent manner. ResMΦ exposed 12/15-LO-derived oxidation products of phosphatidylethanolamine (oxPE) on their plasma membranes and thereby generated a sink for distinct soluble receptors for ACs such as milk fat globule-EGF factor 8, which were essential for the uptake of ACs into inflammatory monocytes. Loss of 12/15-LO activity, in turn, resulted in an aberrant phagocytosis of ACs by inflammatory monocytes, subsequent antigen presentation of AC-derived antigens, and a lupus-like autoimmune disease. Our data reveal an unexpected key role for enzymatic lipid oxidation during the maintenance of self-tolerance.